Metafora pada Lirik Lagu Karya Fiersa Besari sebagai Alternatif Bahan Ajar Siswa SMA - Mawarsih, Putri Beny; Nadzifah, Hidayatun; Darni, Darni (Universitas Muhammadiyah Surabaya, 2024)
The aim of the current research is to conduct an analysis of Indonesian song lyrics that contain metaphors in the lyrics, and then that data is collaborated with education materials in school. The research method used is a qualitative research method and is descriptive in nature. The focus of this research is to examine metaphorical expressions in song lyrics. The data collection technique used is in the form of notes from the results of the song lyrics and documentation of the song lyrics being analyzed. Researchers chose qualitative research with content analysis because content analysis is used to examine text, images, or symbols and documents in content analysis are a form of symbolic representation that can be stored or documented for later analysis. Language style is correlated with the feelings and experiences of the song lyricist. In the process of analyzing the data, the knife used was Michael Riffatere's semiotic study which divides the study of beauty in song lyrics into four parts. The results of the research show that there are 16 metaphorical words in Indonesian song lyrics.